Using Genomics as a decision support tool for smallholder pig enterprises in Uganda (UPG) - Marshall, Karen; Babigumira, Brian; Ouma, Emily; Lule, Peter M.; Rutto, Erick; Wurzinger, Maria; Sölkner, Johann (2023)
The study applies system analysis methods to smallholder pig enterprises in two districts of Uganda to collect and analyse primary data on household demographic characteristics, pig production and management practices, ownership and control of household assets and livelihoods., The project's specific objective is to increase the productivity and profitability of Uganda smallholder pig enterprises through identifying the most appropriate pig breed-type(s); developing a genetic improvement strategy to ensure the availability and accessibility of genetically superior pigs; and supporting the uptake and optimal management of the genetically superior pigs by women and men smallholder pig keepers. The aim of collecting this data is to create an evidence base that will support on-farm decisions, service delivery by extension workers and policy formulation for improved productivity and profitability smallholder pig enterprises in Uganda.